Mechanisms Underlying Lumbopelvic Pain During Pregnancy: A Proposed Model - Daneau, Catherine; Abboud, Jacques; Marchand, Andrée-Anne; Houle, Mariève; Pasquier, Mégane; Ruchat, Stephanie-May; Descarreaux, Martin (Frontiers in Pain Research, 2021)
Up to 86% of pregnant women will have lumbopelvic pain during the 3rd trimester of 36 pregnancy and women with lumbopelvic pain experience lower health-related quality of life 37 during pregnancy than women without lumbopelvic pain. Several risk factors for pregnancy-38 related lumbopelvic pain have been identified and include history of low back pain, previous 39 trauma to the back or pelvis and previous pregnancy-related pelvic girdle pain. During 40 pregnancy, women go through several hormonal and biomechanical changes as well as 41 neuromuscular adaptations which could explain the development of LBPP, but this remains 42 unclear. The aim of this article is to review the potential pregnancy-related changes and 43 adaptations (hormonal, biomechanical and neuromuscular) that may play a role in the 44 development of lumbopelvic pain during pregnancy. This narrative review presents different 45 mechanisms that may explain the development of lumbopelvic pain in pregnant women. A 46 hypotheses-driven model on how these various physiological changes potentially interact in the 47 development of lumbopelvic pain in pregnant women is also presented. Pregnancy-related 48 hormonal changes, characterized by an increase in relaxin, estrogen and progesterone levels, 49 are potentially linked to ligament hyperlaxity and joint instability, thus contributing to 50 lumbopelvic pain. In addition, biomechanical changes induced by the growing fetus, can 51 modify posture, load sharing and mechanical stress in the lumbar and pelvic structures. Finally, 52 neuromuscular adaptations during pregnancy include an increase in the activation of 53 lumbopelvic muscles and a decrease in endurance of the pelvic floor muscles. Whether or not a 54 causal link between these changes and lumbopelvic pain exists remains to be determined. This 55 proposed model proposed a better understanding of the mechanisms behind the development of 56 lumbopelvic pain during pregnancy to guide future research. It should allow clinicians and 57 researchers to consider the multifactorial nature of lumbopelvic pain while taking into account 58 the various changes and adaptations during pregnancy.